Effect of vineyard floor management practices on water use: A case study at a terroir of the "Dão" winegrowing region in Portugal - Marques, F. (2016)
Aiming to evaluate the effect of vineyard floor management practices on water use and vine performance, a field experiment was carried out at the Dão Wine Research Station, located at Nelas, Center Portugal. The experiment was set up in 2010 in a mature vineyard planted with the red grape variety ‘Touriga Nacional’, using a 2x2 factorial design with the following treatments: inter-row soil management (permanent resident vegetation vs. soil tillage) and undervine floor management (mulch vs. herbicide). In this paper it will be presented data from 2013 growing season (four seasons after experiment setup). The volumetric soil moisture, assessed with a capacitance probe to a 1.5 m depth, showed a decreasing pattern throughout the growing season in all treatments with the resident vegetation presenting lower values as compared to the tillage treatment, while no significant differences were observed between the two undervine floor management practices. From budburst to flowering the resident vegetation treatment showed a higher soil water depletion (up to 1.5 m depth) than the tillage treatment but the relative situation was reversed during the flowering-veraison period, while no significant differences were observed during the ripening period. Vine stem water potential values showed a decreasing pattern along the season attaining very low values during September but with no significant differences between treatments. In general the soil management practices did not significantly affect vine vigor, yield and berry composition however, since these results are only from one season, further data analysis in ongoing in order to allow stronger conclusions.